PENGARUH LAMA PERENDAMAN BENIH DENGAN TRIAKONTANOL DAN BERBAGAI KONSENTASI ZAT ATONIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN WORTEL - EKO HARTOYO (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2015)
The research conducted was to evaluate the effect of triatikontanol submerged time and atonik concentration to the growth and yield of carrot (Daucus carrota L.). the research has been done at Tawangmangu, Karanganyar,on altitude 1200 m above sea levels, ad andosol soil type. The reasearch applied factorial design arranged in Randomized Completely Block Design (RCBD) consisted of two factors and three replications. The first factoe, triankontanol submerged time (L) consisted of three levels (0,5 ; 1,0 and 1,5 time). The second factor, atonik concentrartion (K) consisted of four levels ( 0 cc/1 ; 0,5 cc /1 ; 1,25 CC / 1 and 2,0 CC / 1 ). The research concluded that : Triankontanol submerged time feect was significant to the height of plant, diameter of tuber, weight of tuber per plant, long of tuber, volume of tuber, fresh weight of crown, dry weight of crown and weight of tuber per plot. Atonik concentration treatment effect was signifikan to the height og plant, diameter of tuber, weight of tuber per plant, long of tuber, volume of tuber, fresh weight of crown, dry weight of crown and weight of tuber per plot. Interaction between of triankontanol submerged time and antonik concentration treadment effect was significant to weight of tuber plant, long of tuber, volume of tuber, fresh weight of crown, dry weight of crown and weight of tuber per plot. The highest weight of tuber 4,69 kg/plot (31,26 ton/ha), was found at the treatment L3K2 (1,5 long time triakontanol submerged and 1, 25 cc/l atonik concentration). The lowest weight of tuber 3, 36 kg/plot (22,39 ton/ha), was found at the treatment L1K0 (0,5 long time triankontanol submerged without atonik).